Research of the photovoltaic properties of anodized films of Sn - Afanasyev, D.A.; Ibrayev, N.Kh.; Omarova, G.S.; Smagulov, Zh.K. (IOP Conf. Series: Materials Science and Engineering, 2015)
The results of studies of photovoltaic properties of solar cells based on porous tin oxide films, sensitized with an organic dye are presented. Porous films were prepared by electrochemical anodization of tin in alkaline electrolytes based on aqueous solution of NaOH and aqueous ammonia NH4OH. It was found that the time of anodizing of the Sn films affects on conversion efficiency of light energy into electrical energy. Increasing of the sorption time leads to an increase of the number of molecules on the surface of the porous film. For the solar cell based on tin oxide there is a strong dark current, which significantly reduces the efficiency of conversion of light energy into electrical energy.
Keywords: research; photovoltaic properties; anodized films of Sn